Analysis Of The Role Of Social Media In Marketing Communication Strategies And Their Impact On Consumer Loyalty - Naufal Rafif Rabbani; Ihwan Susila; Edy Purwo Saputro (Green Publisher Indonesia, 2024)
In today's digital era, social media has become a key tool in marketing communication strategies, allowing companies to interact more intensively with consumers. However, a deep understanding of the specific elements that drive customer engagement and loyalty through social media is still needed. This study aims to analyze the influence of Trendiness, Interactivity, Informativeness, Advertisement, Entertainment on Customers Engagement and Customers Loyalty. The research method in this study uses a questionnaire as a measuring instrument. The population in this study were all consumers as users of the Rucas brand, male and female aged 15-40 years, the sample in this study was 124 people. This type of research is explanatory research with an analysis tool, namely PLSSEM (Partial Least Square - Structural Equation Modeling). The results of data analysis show that the influence of Trendiness, Advertisement, and Entertainment on Customers Engagement has a positive and significant effect, then Trendiness, Advertisement, and Entertainment on Customers Loyalty have a positive and significant effect. However, Interactivity and Informativeness have no effect on Customers Engagement. The variables Interactivity and Informativeness on Customers Loyalty also have no positive and insignificant effect